2019
DOI: 10.1111/poms.12998
|View full text |Cite
|
Sign up to set email alerts
|

Production Coopetition Strategies for Competing Manufacturers that Produce Partially Substitutable Products

Abstract: T his study examines the strategic choices of two rival manufacturers between competition and coopetition. A complex relationship exists between these two firms, who manufacture substitutive products. In addition, each of these firms has an option to purchase (or sell) a key component from (or to) the other. We develop a benchmark competition model and two coopetition models in which the manufacturers compete for end-customer demand while simultaneously collaborating on component production through wholesaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 47 publications
1
46
0
1
Order By: Relevance
“…Where = 1, 2 and = 3 − . Such demand functions have been commonly used in the economics and marketing literatures to capture competition between multiproduct retailers (Trivedi, 1998;Feng and Lu, 2012;Huang et al, 2013;Chen et al 2019a).…”
Section: Figure 1 Online Platform Selling Formatmentioning
confidence: 99%
“…Where = 1, 2 and = 3 − . Such demand functions have been commonly used in the economics and marketing literatures to capture competition between multiproduct retailers (Trivedi, 1998;Feng and Lu, 2012;Huang et al, 2013;Chen et al 2019a).…”
Section: Figure 1 Online Platform Selling Formatmentioning
confidence: 99%
“…In the symmetric structure (Nash) model, a Nash equilibrium exists between the two supply chain members. We follow the standard game theoretical approach reported in the literature (Chen et al 2019;SeyedEsfahani et al 2011;Chen and Wang 2015) to describe the decision sequence in the Nash model.…”
Section: Symmetric Structure Modelmentioning
confidence: 99%
“…Shang and Wang (2015) stated that risk aversion and negotiation power have a profound effect on the selection of optimal parameters in the profit-sharing contract negotiation. Chen et al (2019) found that along with the external market characteristics and internal operational capabilities, negotiation power plays a significant role in the supply contract negotiation with a supplier, who is also its market rival.…”
Section: Nmentioning
confidence: 99%